(s-6)+(8s+4)=

Simple and best practice solution for (s-6)+(8s+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (s-6)+(8s+4)= equation:


(s-6)+(8s+4)=0

We simplify the equation to the form, which is simple to understand
(s-6)+(8s+4)=0

Remove unnecessary parentheses
s-6+(8s+4)=0

Remove unnecessary parentheses
+s-6+8s+4=0

We move all terms containing s to the left and all other terms to the right.
+1s+8s=0+6-4

We simplify left and right side of the equation.
+9s=+2

We divide both sides of the equation by 9 to get s.
s=0.22222222222222

See similar equations:

| -120/(-20)= | | 10+0.10a=0.35a | | 97-5*x=48+2*x | | 12(p-2.33)=8 | | x^2+15+40=4 | | 10+0.10a=0.35 | | 22-s/7=-5 | | 8×5.5/11 | | -60-7n=4+9n | | 1.5x+20= | | 0.5x^2=8x-0.625 | | 3(x-4)-5x=-2x+10 | | y=3(10-2) | | X-0.20x=485.20 | | y=3(8-2) | | 12/(-2)= | | .29x=125-x | | y=3(2-2) | | n-2.2=3.1 | | 52-(2x+6)=2(x+8)+x | | -7-3v=2v+45 | | X+.20x=485.20 | | 2n=10.6 | | 8K=76I | | -8-5x=12-19x | | x/9/2.x | | 4z+7=9z-20 | | 43.25=7+1.25m | | 6x^2-32x+4=0 | | x^2-36=100 | | y=6x^2-32x+4 | | 2x+2=10x+3 |

Equations solver categories